Aerodynamic analysis of a 2-man bobsleigh - Lewis, O. (2006)
One of the fastest and most exciting winter sports is bobsleighing. Every last one hundredth of a second is of importance. Boblsleighing originally started in the end of the 19th century and especially since the 1950's has developed into a hi-tech sport. Today NASCAR and Formula One technology is used to build the fastest sleds. After the start the only force propelling a bobsleigh is the force of gravity and if no driving mistakes are made only the aerodynamic drag and friction with the ice act against the sled. A simple bobsleigh equation of motion shows that the aerodynamic force during a run has a significant influence on the finish times. A drag reduction of three percent is predicted to reduce the final time by one tenth of a second. The basic shape of a bobsleigh is determined by the rules. Slight changes can be made to for instance the bumpers, the gap between front and rear cowling, the shape of the nose and the edges of the spring leafs and runner carriers. What severely limits changes to an existing bob is the fact that the bob should have convex shape and that no holes or vortex generators are allowed. To study the flow several measurement and visualization techniques have been applied. To measure the forces a six component balance was used. Oil flow visualization has been applied to investigate the surface flow. PIV has been used to get both qualitative and quantitative information. Wool tufts and a microphone were used to localize vortices and finally CFD calculations have been performed. The steady RANS equations with the realizable k-å turbulence model were solved on half the model, because it is assumed the flow is symmetrical. The calculated flow shows good agreement with theory and windtunnel results, both qualitatively and quantitatively. Much effort was concentrated on the transition between front and rear cowling. This is because it is an area that is relatively easy to adapt, so any found improvements could be applied at the Olympic Games by the Dutch bobsleigh teams. Also numerous other variations have been researched, like the position of the crew and rotation of the nose. From the results found it can be concluded that the gap between front and rear cowling should be partially closed, leaving a gap at the top. Other factors that can reduce the drag of a bobsleigh are selecting a low drag helmet, optimizing the position of the crew, rounding the edges of the runner carriers and keeping the nose as smooth as possible. Several topics require further research. For instance the effect of the shape of the nose on aerodynamic drag. Also the drag of the axles, leaf springs, runners and runner carriers should be analyzed and improved if possible.